Achievement Motivation as Antecedents of Quality Improvement of Organizational Human Resources - Any Werdhiastutie; Fendy Suhariadi; Sri Gunani Partiwi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Achievement motivation is closely related to success and success or individual spirit in achieving a goal or success. David McClelland is famous for the theory of the need to achieve achievement that states that motivation varies, according to the strength of one's need for achievement. Motivation of work is a strong desire for humans to do a job related to the goals and needs to be achieved. Achievement motivation should also be designed according to the strategy model. Analysis of achievement motivation will lead to the form of evaluation on human resources and other potentials owned by the organization appropriately. Achievement motivation is intended to encourage the elements of improvement that will be applied and evaluated as the stage of improving the quality of human resources organization. Individual needs are met able to improve performance. Individuals in this study are motivated on the basis of achievement to be achieved based on the needs of each individual. Achievement motivation implanted in work system according to individual needs and desires is found able to produce greater individual performance improvement